2020
DOI: 10.1007/s00404-020-05880-0
|View full text |Cite
|
Sign up to set email alerts
|

Demand for integrative medicine among women with breast and gynecological cancer: a multicenter cross-sectional study in Southern and Northern Germany

Abstract: Purpose The aim of this multicenter cross-sectional study was to analyze a cohort of breast (BC) and gynecological cancer (GC) patients regarding their interest in, perception of and demand for integrative therapeutic health approaches. Methods BC and GC patients were surveyed at their first integrative clinic visit using validated standardized questionnaires. Treatment goals and potential differences between the two groups were evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 61 publications
(82 reference statements)
1
17
0
1
Order By: Relevance
“…A survey study contemporary with DELCaP and MARIE studies showed that more than a quarter of patients used complementary and alternative medicine (CAM) during oncology therapy to alleviate the side effects of treatment [23]. A present multicenter cross-sectional study in Southern and Northern Germany showed 70.4% of breast patients wanted to reduce the side effects of conventional therapy with CAM [24]. These patients were generally more likely to interrupt tumor therapy than non-AVS users because of the side effects of treatment.…”
Section: Discussionmentioning
confidence: 81%
“…A survey study contemporary with DELCaP and MARIE studies showed that more than a quarter of patients used complementary and alternative medicine (CAM) during oncology therapy to alleviate the side effects of treatment [23]. A present multicenter cross-sectional study in Southern and Northern Germany showed 70.4% of breast patients wanted to reduce the side effects of conventional therapy with CAM [24]. These patients were generally more likely to interrupt tumor therapy than non-AVS users because of the side effects of treatment.…”
Section: Discussionmentioning
confidence: 81%
“…This is in accordance with the findings of other studies that have reported that reducing tumor progression is a major long-term treatment goal for breast cancer patients who use integrative medicine. 35 However, it is difficult for patients to draw firm conclusions on whether this therapy goal has been achieved, and no links have been established between the use of integrative medicine and disease prognosis or mortality. 15 However, a fear of tumor recurrence has been found to be associated with the use of CAM by patients.…”
Section: Discussionmentioning
confidence: 99%
“…Darüber hinaus werden komplementäre Methoden oft mit dem Ziel eingesetzt, die Lebensqualität zu verbessern, therapieinduzierte Symptome zu lindern und/oder das Immunsystem zu stärken [6].…”
Section: Merkeunclassified